Site suitability analysis for Bay scallop aquaculture and implications for sustainable fisheries management in the Ha Long Bay archipelago, northern Vietnam - Michele, Marconi; Thuoc, Pham; Tien Canh, Nguyen; Thi Khanh, Pham; Fausto, Marincioni (JNRD - Journal of Natural Resources and Development, 2013)
Mollusc culture if properly managed, may help decrease capture fisheries over-exploitation in Vietnam, and possibly become an alternative income for local fishermen. The definition and characterization of zones suitable for aquaculture is pivotal for its success and sustainable development, and this study aims at determining the suitability of Argopecten irradians (Bay scallop) culture in the Ha Long Bay Archipelago. Temperature, salinity, chlorophyll-a, total suspended solid and bathymetry, were compiled in an environmental suitability model. Distance of culture sites from landing points and fish markets were instead grouped in an infrastructural suitability model. In both models, developed with Geographic Information Systems, the suitability scores were ranked on a scale from 1 (unsuitable) to 6 (very-highly suitable). Results showed that 98 % of the studied area is environmentally suitable for such culture. However, overlaying the infrastructural factors the suitable zone decrease to 38 %. Advantages and disadvantages of two management options were then discussed: (a) strengthening fisheries infrastructures or (b) developing post harvesting processing plants.